Variability in morphology and biochemical constituents in wheat germplasm with special reference to spot blotch - Verma, Surdeep K.; Biswas, SK; Kumar, Virendra; Lal, Kishan; Kumar, Santosh; Bahar, Javed; Kanchan, Charul (Bangladesh Journal of Botany, 2018)
Variability among 11 wheat germplasms viz. KRL 283, KRL 330, KLP 402, WH 1112, DBW 111, NW 5055, RAJ 4270, KRL 327, KRL 331, KRL 210 and KHARACHIA 65 were studied considering their morphology and the presence of bio-molecules. The results revealed that all these germplasms possess variability in terms of the mentioned parameters. The germplasm, RAJ 4270 and KRL 331 were medium in plant height with synchronous tillering habit while the majority were dwarf in nature except KHARACHIA 65. The germplasm also showed different response to spot blotch at different stages of plant growth, reflecting 11.04 - 15.40% at booting, 21.65 - 28.75 at flowering and 30.5 - 40.78 % at milking stages. Among all the germplasms, NW 5055 showed minimum disease severity, representing 11.04, 21.65 and 30.5% at booting, flowering and milking stages, respectively. The possible mechanism of resistance revealed that the presence of higher amount of total phenol and soluble protein, resulted lower disease incidence. The germplasm NW 5055 contained maximum amount of soluble protein reflecting, 30.27 mg/g at seedling, 29.54 mg/g at booting, 28.48 mg/g at flowering and 28.25 mg/g at milking stage. Similarly, total phenol content was also found maximum 2.87 mg/g at seedling, 2.73 mg/g at booting, 2.50 mg/g at flowering and 2.35 mg/g at milking stage in the same variety. Correlation between total phenol and soluble protein with disease severity at different stages of plant growth showed that there was a negative correlation in almost all the germplasms.